Analysis of challenge request success according to contextual variables in elite badminton - Primo, L.; Gutiérrez-Suárez, A.; Gómez, M. Á. (German Journal of Exercise and Sport Research, 2019)
Badminton has evolved into a blink-and-miss event, with powerful smashes dominating rallies. Due to the fact that the speed of smashes has increased, there are controversial decisions when the shuttlecock hits the ground during the match. Therefore, the aim of the present study was to identify the importance of challenge request effectiveness in elite badminton according to contextual-related variables. The sample was composed of 56 shuttlecock challenges requested during 20 matches (quarter-final, semi-final or final matches) from the Olympic Games (Rio de Janeiro, 2016) and the Word Badminton Championship (Glasgow, 2017). The Crosstabs-Command and the Binomial logistic regression were applied in order to identify the interactive effects on challenge success of each contextual variable (gender, requester player, next point winner, score-line, game, game interval, games in favor, challenges left per game, match-outcome and player`s international experience). The main results identified that the success of a challenge is affected by the request with less efficiency when the player requests the hawk-eye (odds ratio [OR]=0.65) and when the player that request the hawk-eye is the loser of the match (OR=0.21). The identified trends allow players to improve strategic plans that involve selecting the most appropriate moment to request the calling Line Review. Badminton stellt zunehmend hohe kognitive Anforderungen an den Spieler. Da die Schlaggeschwindigkeiten beim Smash zunehmen, entstehen kontroverse Entscheidungen über das Auftreffen des Balles im Feld. Hierzu besteht neuerdings die Möglichkeit für die Spieler, eine optische Entscheidungsprüfung zu beantragen. Das Ziel der vorliegenden Studie bestand darin, die Effektivität dieser beantragten Prüfung ("challenge request effectiveness") in Abhängigkeit von verschiedenen Variablen zu kontextualisieren. Die Stichprobe bestand aus 56 Challenges aus 20 Matches (Viertelfinale, Halbfinale, Finale) der Olympischen Spiele (Rio de Janeiro, 2016) und der Badminton Weltmeisterschaft (Glasgow, 2017). Mittels binominaler logistischer Regression wurden die Interaktionseffekte zwischen dem Challenge-Erfolg und weiteren Variablen (Geschlecht, folgender Punktgewinner, Spielfeldlinie, Spielintervall, Spielstand, verbleibende Anzahl an Challenges, Spielergebnis und Spielerfahrung der Spieler) berechnet. Das zentrale Ergebnis besteht darin, dass der Challenge-Erfolg abfällt, wenn der Spieler eine Prüfung durch das technische hawk-eye erfragt (OR=0,65) und wenn der beantragende Spieler der anschließende Verlierer des Matches ist (OR=0,21). Diese Trends erlauben eine strategisch bessere Planung der beantragten Entscheidungsprüfungen.